Screening for inborn errors of metabolism in high-risk children: a 3-year pilot study in Zhejiang Province, China - Huang Xinwen; Yang Lili; Tong Fan; Yang Rulai; Zhao Zhengyan (BMC, 2012)
Abstract Background Tandem mass spectrometry (MS/MS) has been available in China for 8 years. This technique makes it possible to screen for a wide range of previously unscreened inborn errors of metabolism (IEM) using a single test. This 3-year pilot study investigated the screening, diagnosis, treatment and outcomes of IEM in symptomatic infants and children. Methods All children encountered in the Newborn Screening Center of Zhejiang Province during a 3-year period with symptoms suspicious for IEM were screened for metabolic diseases. Dried blood spots were collected and analyzed by tandem mass spectrometry. The diagnoses were further confirmed by clinical symptoms and biochemical analysis. Neonatal intrahepatic cholestasis caused by citrin deficiency, ornithine transcarbamylase deficiency and primary carnitine deficiency were confirmed by DNA analysis. Results A total of 11,060 symptomatic patients (6,720 boys, 4,340 girls) with a median age of 28.8 months (range: 0.04-168.2 months) were screened. Among these, 62 were diagnosed with IEM, with a detection rate of 0.56%. Thirty-five were males and 27 females and the median age was 3.55 months (range 0.07-143.9 months). Of the 62 patients, 27 (43.5%) had aminoacidemias, 26 (41.9%) had organic acidemias and nine (14.5%) had fatty acid oxidation disorders. Conclusions Because most symptomatic patients are diagnosed at an older age, mental retardation and motor delay are difficult to reverse. Additionally, poor medication compliance reduces the efficacy of treatment. More extensive newborn screening is thus imperative for ensuring early diagnosis and enhancing the treatment efficacy of IEM.